The Digital Media Impact On The Well-Being Of Children: A Systematic Literature Review - Sakti Kaloeti, Dian Veronika; Ediati, Annastasia; Hanafi, Sekar; Tahamata, Valentino Marcel; Kurnia, Ayu; Manalu, Rouli (Indonesian Journal of Early Childhood Education Studies, 2021)
Abstract People may focus on the adverse effect of digital media use among children. It may lead to a lower level of the child’s well-being and kinds of negative psychological implications. In the other hand, the use of digital media also generates some positive impacts on a child’s well-being. Some contextual factors should be discovered in mediating this gap. A systematic literature review was conducted and generated 532 papers. Studies were involved if they used any kinds of digital media among the children. The study methodology was aligned by the PRISMA guidelines for systematic literature review. Screening for those articles remained 21 articles which met the inclusion criteria. This review provides both negative and positive effects of digital media use among the children and its implication for their well-being. The review draws some contextual factors in inflicting the adverse effect of digital media use, and it might some key-points to overcome the negative effects of digital media use on a child’s well-being. Discussion: Some intervention had been conducted to overcome the negative effects of digital media use targeted to the children and parents. This review brings insight for future study to arrange the comprehensive intervention for children, parents, teachers, as well as a peer.